2021
DOI: 10.1002/cptc.202100178
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Fluctuations in Conjugation and their Effect on Calculated Excitation Energies: A Case Study on the Astaxanthin Carotenoid

Abstract: A popular approach to the calculation of molecular excitation energies is to consider only equilibrium geometries and neglect the effects of thermal motion. Although this static approach is sensible for molecules with distinct potential-energy minima, its adequacy relative to dynamical approaches appears not to have been thoroughly tested. Here, we report a case study investigating how thermal motion accounted for by molecular dynamics simulations influences the optically bright state of astaxanthin, a caroten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 110 publications
0
8
0
Order By: Relevance
“…In addition, errors produced by using different sizes of basis sets are in general higher than 0.01 eV. For instance, differences obtained by the selection of different basis sets with different density functionals for the closely related astaxanthins may reach 0.04 eV [6]. However, if ΔE values are extrapolated for higher number of carbon atoms ns, the value of ΔE becomes more significant.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, errors produced by using different sizes of basis sets are in general higher than 0.01 eV. For instance, differences obtained by the selection of different basis sets with different density functionals for the closely related astaxanthins may reach 0.04 eV [6]. However, if ΔE values are extrapolated for higher number of carbon atoms ns, the value of ΔE becomes more significant.…”
Section: Resultsmentioning
confidence: 99%
“…At this point, it is worth to compare the results presented herein with that found in the literature. In particular, Wang and Durbeej, found that considering thermal motion on the calculated excitation energies of astaxanthin carotenoids cannot be ignored, since the mean ΔE value for different functionals were found to be around 0.03–0.04 eV, depending on the composition of the density functional (only B3LYP density functional shows ΔE value around 0.01 eV) [6]. It should be noted, however, that there are some discrepancies in the calculation methods used in the present study and that of Wang et al, in terms of the calculation of excited electronic states (double hybrid versus global hybrids) and the calculation of the MD trajectories (extended tight binding for 200 ps vs. global hybrids for 20 ps) [6].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations